Effects of BaTiO3 doped on structural and dielectric properties of Bi0.5(Na0.80K0.20)0.5TiO3 ceramic. (26th April 2017) - Kamnoy, Manlika; Sutjarittangtham, Krit; Parjansri, Piewpan; Intatha, Uraiwan; Eitssayeam, Sukum; Raengthon, Natthaphon
ABSTRACT: We studied the effects of BaTiO3 (BT) seed nano-crystals on dielectric properties and phase transition behavior of Bi0.5 (Na0.8 K0.2 )0.5 TiO3 (BNKT) ceramics. The BaTiO3 seed nano-crystals were used as nuclei, which acted as templates for starting materials to form perovskite phase. In this study, the BT seed nano-crystals were prepared by the molten salt technique. Eutectic mixtures of NaCl-KCl (1:1 by mole) were used as the flux. Various concentrations of BT seed nano-crystals were mixed with other precursors required for formation of BNKT phase, which was prepared by the solid-state method. Addition of BT seed nano-crystals enhanced the electrical properties of ceramics. The sample with 8 mol% BT seed nano- crystals exhibited highest value of dielectric constant ( ϵr ) at maximum temperature of 6700. The grain size significantly decreased with increasing concentration of BT seed nano-crystals. The relaxor ferroelectric behavior was also observed with the diffuseness parameter (γ) value being close to 2.